Vaginal bacteria of healthy cats during different stages of their oestrous cycle - Maksimovic, A; Nurkic, M; Maksimovic, Z; Rifatbegovic, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Little is known about vaginal and uterine bacteria in clinically healthy cats and their correlation with different stages of the oestrus cycle. The differences in vaginal bacterial flora between household and stray queens remains unknown. The aim of this study was to investigate the occurrence of vaginal and uterine bacteria in clinically healthy household and stray queens and to correlate culture findings with specific stages of the oestrous cycle. Vaginal and uterine samples from 40 clinically healthy queens were collected for isolation of bacteria and cytological examination. Bacteria were isolated from 31 vaginal swabs (77.5%) from stray (16/20; 80%) and household (15/20; 75%) cats. The isolates were more frequently detected in pure culture (18/31; 58%) than in mixed cultures (13/31; 41.9%). Streptococcus spp. was the most commonly identified bacteria (n = 16; 51.6%), followed by coagulase negative Staphylococcus spp. (n = 15; 48.4%) and E. coli (n = 12; 38.7%). A mixed bacterial culture of E. coli and Streptococcus spp. was commonly detected (50%), mainly in households (66.7%), whereas a mixed culture of Staphylococcus spp. and Streptococcus spp. (41.6%) was commonly isolated from stray cats (60%). The frequency of isolation of pure or mixed bacterial cultures and the isolates did not vary significantly during the different stages of the oestrus cycle. All uterine samples tested were negative for bacteria. This study identified the most common bacteria in the vagina of clinically healthy cats. The isolation of vaginal bacteria in pure or mixed cultures should be considered as normal finding. The stage of the oestrous cycle apparently does not affect vaginal bacterial flora. Vaginal bacteria may differ between stray and households cats. No bacteria can be isolated from the uterus of clinically healthy cats.